SYNTACTICAL CONVERSATIONAL ERRORS: DOCUMENTATION ON DELIVERY OF COMPETENT IN DIVERGENT SITUATIONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The target of this study is to reach the most recurrently occurring syntactical errors committed by competent who are affiliated with language field. English in Pakistan is calculated as an official and academics language as is in many countries. The main intension behind conducting this type of research is to explore unintentional speaking errors committed by learner. In Pakistan, distinct languages are spoken, if English is spoken in Sindh, it is spoken as second language or third language, as mother tongue is Sindhi and national language is Urdu, same is in Punjab and in other provinces of Pakistan. Hence, there is an impact of each first language on target language. Resultantly, it shows some errors, it may be syntactical errors, grammatical or phonological errors. In this study, error analysis theory, by Gas & Selinker in 2008 through different phases named, 1: collecting data 2: identifying errors 3: classifying error4: quantifying error 5: analyzing errors 6: remediation was used as framework.15 professionals were selected randomly with probability sampling. Communication sessions were conducted with them with semi-structured based interviews. This study deals with qualitative descriptive approach. After applying CICQAR process of error identifier, it is found that even professionals make syntactical error in their communication, most common error was found structural and tenses errors, that speaker does sometimes unintentionally. Researchers have identified and gave suggestions that how to overcome these errors? Findings of this study show that during communication many intentional and unintentional errors occur, these errors may be due to little cognizance of grammar, structure of the sentence or it may happen deliberately.